Efficiency Rules for the Organisation and Functioning of Public Administration in the Views of Professor Stanisław Kasznica (Contemporary Central & East European Law, 2024)
This article refers to the issue of the administrative apparatus system in the views of Professor Stanisław Kasznica. On their basis, an attempt was made to reconstruct efficiency guidelines concerning the formation of public administration structures, relations between them as well as administrative tasks and competences. A catalogue of these praxeological rules justifies the claim that the Professor’s views remain fundamentally up-to-date both for the contemporary science of administrative law and in the sphere of administrative science.